Characteristics of lung cancer in idiopathic pulmonary fibrosis with single lung transplant versus non-transplanted patients: a retrospective observational study. Issue 1 (21st June 2020) - Gershman, Evgeni; Zer, Alona; Pertzov, Barak; Shtraichman, Osnat; Shitenberg, Dorit; Heching, Moshe; Rosengarten, Dror; Kramer, Mordechai
Abstract : Background: Patients with idiopathic pulmonary fibrosis (IPF) have significantly higher incidence of lung cancer (LC) relative to the general population. There is a further increase in LC incidence in patients with IPF subsequent to lung transplant, specifically in patients with IPF undergoing single lung transplant. Objectives: To examine the incidence and characteristics of LC in patients with IPF during follow-up and after lung transplantation (LTX). Methods: We conducted a retrospective analysis of all patients with IPF diagnosed with LC in Rabin Medical Center, Israel, over an 11-year period. We compared the characteristics of transplanted patients with IPF diagnosed with LC to patients with IPF who did not undergo lung transplant. Data were accessed from database registries using the words 'fibrosis', 'lung-cancer' and 'lung-transplantation'. Demographic parameters included age, gender and smoking history (pack years). Clinical-pathological parameters included lapse in time from IPF diagnosis to LC, type of malignancy, affected pulmonary lobe, and stage at diagnosis, oncological treatment and survival. Results: Between 2008 and 2018, 205 patients with IPF underwent lung transplantation at our medical centre. Double LTX was performed in 83 and single LTX in 122 cases. Subsequently, 15 (12.3%) single LTX patients were diagnosed with LC during the study period. During the same period, of 497 non-transplanted patients with IPF followed in our centre, 45 (9.1%) were diagnosed with LC. In all 15 transplanted patients with IPF, LC was diagnosed exclusively in the native fibrotic lung. LC incidence was higher in the transplanted as compared with the non-transplanted group, but this difference did not reach statistical significance (OR=0.7, 95% CI 0.38 to 1.32, p=0.28). At LC diagnosis, the non-transplanted group was older than the transplanted group with average age of 67.7 versus 60.8 years, respectively (p=0.006). Both groups showed male predominance. In both groups, LC was primarily peripheral, lower lobe predominant and most frequently squamous cell carcinoma. The median survival time after LC diagnosis was 4 months in the transplanted group and 11 months in the non-transplanted group (p=0.19). Multivariate analysis showed improved survival in the non-transplanted group among those patients who received oncological treatment. Conclusion: Chest CT should be performed regularly in order to evaluate IPF patients for potential LC. Single lung transplant IPF patients face an increased risk of post-transplant LC in the native fibrotic lung. Where practicable, IPF patients should be prioritised for double lung transplant.